Helicobacter pylori adhesin HopQ disrupts trans dimerization in human CEACAMs. - Moonens, Kristof; Hamway, Youssef; Neddermann, Matthias; Reschke, Marc; Tegtmeyer, Nicole; Kruse, Tobias; Kammerer, Robert; Mejias-Luque, Raquel; Singer, Bernhard B.; Backert, Steffen; Gerhard, Markus; Remaut, Han (EMBO Journal, 2018)

How many protein molecules are secreted by single Helicobacter pylori cells: Quantification of serine protease HtrA - Neddermann, Matthias; Backert, Steffen (Cellular Microbiology, 2019)
Infection with Helicobacter pylori represents a major risk for developing peptic ulcer disease, gastric adenocarcinoma, and various other gastric and nongastric sicknesses. A series of H. pylori virulence factors can be secreted into the cell culture supernatant, and the secretome contains more than 100 different proteins. However, the quantities of proteins secreted by the bacteria over time are unknown. One of these factors is the serine protease high-temperature requirement A (HtrA), encoded by an essential bifunctional gene with crucial intracellular and extracellular activities. We have demonstrated recently that secreted HtrA can cleave off the ectodomains of the tight junction proteins occludin and claudin-8, as well as of the tumour suppressor and adherens junction protein E-cadherin on polarised gastric epithelial cells. The exact mechanism of secretion and the quantity of secreted HtrA, however, have not been studied in detail. Here, we applied protein purification and quantitative Western blotting to determine the number of HtrA molecules secreted by H. pylori cells in liquid culture during a time course. Over a period of 8 hr, actively dividing bacteria secreted HtrA at a similar rate, on average about 9,600 HtrA molecules per cell. We determined minor variation over time corresponding to 9,931 ± 1,768 at an OD600 of 0.4 after 2 hr, 9,403 ± 2,356 2 hr later, and 9,644 ± 2,067 molecules per cell after 8 hr of culturing, when the culture had reached an OD600 of 0.8. This is the first report on the quantification of a secreted virulence protein from the important gastric pathogen H. pylori. Because HtrA has been considered as a promising new target for antibacterial therapy, knowledge about secreted protein quantities is crucial for optimising corresponding treatment regimes.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Helicobacter pylori; secretion; serine protease HtrA; signalling; VacA

Interaction of Helicobacter pylori with Toll-Like receptors: role in infection control and resolution of inflammation - Backert, Steffen; Suneesh Kumar, Pachathundikandi; Neddermann, Matthias; Lind, Judith; Tegtmeyer, Nicole (HELICOBACTER, 2019)
CRIS-Team WoS Importer:2019-10-04

Pathogenesis of Helicobacter pylori infection - Backert, Steffen; Neddermann, Matthias; Maubach, Gunter; Naumann, Michael (Helicobacter, 2016)
Helicobacter pylori is estimated to infect more than half of the worlds human population and represents a major risk factor for chronic gastritis, peptic ulcer disease, MALT lymphoma, and gastric adenocarcinoma. H. pylori infection and clinical consequences are controlled by highly complex interactions between the host, colonizing bacteria, and environmental parameters. Important bacterial determinants linked with gastric disease development include the cag pathogenicity island encoding a type IV secretion system (T4SS), the translocated effector protein CagA, vacuolating cytotoxin VacA, adhesin BabA, urease, serine protease HtrA, secreted outer membrane vesicles, and many others. The high quantity of these factors and allelic changes in the corresponding genes reveals a sophisticated picture and problems in evaluating the impact of each distinct component. Extensive work has been performed to pinpoint molecular processes related to H. pylori-triggered pathogenesis using Mongolian gerbils, mice, primary tissues, as well as novel in vitro model systems such as gastroids. The manipulation of host signaling cascades by the bacterium appears to be crucial for inducing pathogenic downstream activities and gastric disease progression. Here, we review the most recent advances in this important research area.
Created from Fastlane, Scopus look-up
Keywords: CagA; CagL; gastric cancer; gastroids; HtrA; inflammation; pathogenicity island; signaling; TlpB; type IV secretion system; urease; VacA

Quantification of serine protease HtrA molecules secreted by the foodborne pathogen Campylobacter jejuni - Neddermann, Matthias; Backert, Steffen (Gut Pathogens, 2019)
Background: Campylobacter jejuni is a major food-borne pathogen and a worldwide health threat. Utilizing different virulence factors, C. jejuni invades the host's intestinal epithelial cell layer. One important factor in this process is the serine protease HtrA, which is secreted into the extracellular space, and helps the bacteria to transmigrate across the gut epithelium by cleaving various cell-cell adhesion proteins. The aim of the present study is to quantify the amount of HtrA molecules secreted per bacterial cell in liquid culture and during infection.
CRIS-Team WoS Importer:2019-04-30

Subversion of host kinases: a key network in cellular signaling hijacked by Helicobacter pylori CagA - Tegtmeyer, Nicole; Neddermann, Matthias; Asche, Carmen Isabell; Backert, Steffen (Molecular Microbiology, 2017)
Helicobacter pylori is a paradigm of persistent pathogens and major risk factor for developing severe diseases including adenocarcinoma in the human stomach. An important bacterial factor linked to gastric disease progression is the cag pathogenicity island-encoded type-IV secretion system (T4SS) effector protein CagA. Translocated CagA undergoes tyrosine phosphorylation at EPIYA-motifs and then activates or inactivates multiple host signaling proteins in a phosphorylation-dependent and phosphorylation-independent fashion. In this way, intracellular CagA acts as a ‘masterkey’ or ‘picklock’, which evolved during evolution to hijack key host cell signal transduction functions. Crucial targets of CagA represent a variety of serine/threonine and tyrosine kinases, which control major checkpoints of eukaryotic signaling. Here we review the signal transmission by translocated CagA on multiple receptor kinases (c-Met and EGFR) and non-receptor kinases (Src, Abl, Csk, aPKC, Par1, PI3K, Akt, FAK, GSK-3, JAK, PAK1, PAK2 and MAP kinases), manipulating a selection of fundamental processes in the human gastric epithelium such as cell adhesion, polarity, proliferation, motility, receptor endocytosis, cytoskeletal rearrangements, apoptosis, inflammation and cell cycle progression. This enormous complexity generates a highly remarkable and puzzling scenario during H. pylori infection. The contribution of these signaling pathways to bacterial survival, persistence and gastric pathogenesis is discussed.
Created from Fastlane, Scopus look-up

T4SS-dependent TLR5 activation by Helicobacter pylori infection - Suneesh Kumar, Pachathundikandi; Tegtmeyer, Nicole; Arnold, Isabelle Catherine; Lind, Judith; Neddermann, Matthias; Falkeis-Veits, Christina; Chattopadhyay, Sujay; Brönstrup, Mark; Tegge, Werner; Hong, Minsun; Sticht, Heinrich; Müller, Anne; et al. (Nature Communications, 2019)
Toll-like receptor TLR5 recognizes a conserved domain, termed D1, that is present in flagellins of several pathogenic bacteria but not in Helicobacter pylori. Highly virulent H. pylori strains possess a type IV secretion system (T4SS) for delivery of virulence factors into gastric epithelial cells. Here, we show that one of the H. pylori T4SS components, protein CagL, can act as a flagellin-independent TLR5 activator. CagL contains a D1-like motif that mediates adherence to TLR5+ epithelial cells, TLR5 activation, and downstream signaling in vitro. TLR5 expression is associated with H. pylori infection and gastric lesions in human biopsies. Using Tlr5-knockout and wild-type mice, we show that TLR5 is important for efficient control of H. pylori infection. Our results indicate that CagL, by activating TLR5, may modulate immune responses to H. pylori.
CRIS-Team Scopus Importer:2019-12-27

Toll-like Receptor 5 Activation by the CagY Repeat Domains of Helicobacter pylori - Tegtmeyer, Nicole; Neddermann, Matthias; Lind, Judith; Suneesh Kumar, Pachathundikandi; Sharafutdinov, Irshad; Gutiérrez-Escobar, Andrés Julián; Brönstrup, Mark; Tegge, Werner; Hong, Minsun; Rohde, Manfred; Delahay, Robin M.; Sticht, Heinrich; et al. (Cell Reports, 2020)
Helicobacter pylori (Hp) is an important human pathogen associated with gastric inflammation and neoplasia. It is commonly believed that this bacterium avoids major immune recognition by Toll-like receptors (TLRs) because of low intrinsic activity of its flagellin and lipopolysaccharides (LPS). In particular, TLR5 specifically detects flagellins in various bacterial pathogens, while Hp evolved mutations in flagellin to evade detection through TLR5. Cancerogenic Hp strains encode a type IV secretion system (T4SS). The T4SS core component and pilus-associated protein CagY, a large VirB10 ortholog, drives effector molecule translocation. Here, we identify CagY as a flagellin-independent TLR5 agonist. We detect five TLR5 interaction sites, promoting binding of CagY-positive Hp to TLR5-expressing cells, TLR5 stimulation, and intracellular signal transduction. Consequently, CagY constitutes a remarkable VirB10 member detected by TLR5, driving crucial innate immune responses by this human pathogen.
CRIS-Team Scopus Importer:2020-09-25
Keywords: CagY; flagellin; Helicobacter; innate and adaptive immunity; PAMP; PRR; signal transduction; T4SS; TLR5; type IV secretion